Acute hemorrhagic edema in a nursing infant - An unusual diagnosis - Agarwal, Neha; Taneja, Sunil; Bihari, Saket; Verma, Ashish (Indian Journal of Child Health, 2018)
Acute hemorrhagic edema of infancy is a rare, small vessel vasculitis of young children with characteristic skin findings. We have described an 8-month-old male infant who presented with upper respiratory infection followed by acute onset of generalized swelling of both lower limbs and appearance of erythematous, purpuric, and ecchymotic lesions on the lower limbs, face, and ear lobules. There were no systemic complications and the lesions resolved completely.